Developing Entrepreneurial Intelligence Among Retirees of the Bukittinggi City Government - Stevani Stevani; Vivina Eprillison; Dina Amaluis; Jimi Ronald; Mona Amelia (Universitas PGRI Sumatera Barat, 2024)
While